2023
DOI: 10.3389/fendo.2023.1192625
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus promotes susceptibility to periodontitis—novel insight into the molecular mechanisms

Mingcan Zhao,
Yuandong Xie,
Wenjia Gao
et al.

Abstract: Diabetes mellitus is a main risk factor for periodontitis, but until now, the underlying molecular mechanisms remain unclear. Diabetes can increase the pathogenicity of the periodontal microbiota and the inflammatory/host immune response of the periodontium. Hyperglycemia induces reactive oxygen species (ROS) production and enhances oxidative stress (OS), exacerbating periodontal tissue destruction. Furthermore, the alveolar bone resorption damage and the epigenetic changes in periodontal tissue induced by dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 261 publications
(372 reference statements)
0
11
0
Order By: Relevance
“…For diabetic patients with ≤ 5 missing teeth, patients without cardiovascular disease, non-smoking patients, and patients receiving anti-diabetic drugs, α-carotene, lutein and zeaxanthin, or β-cryptoxanthin was also found to be related to periodontitis. Over 5 missing teeth, cardiovascular disease, smoking, and uncontrolled diabetes are greatly correlated with the higher incidence and progression of periodontitis ( 40 43 ) , which might overshadow or mask the relationship between carotenoid intake and periodontitis. Importantly, these groups of diabetic patients should pay more attention to their oral health, and higher intake of α-carotene, lutein and zeaxanthin, or β-cryptoxanthin may become a reference strategy in hindering the occurrence and development of periodontitis, which requires future studies to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…For diabetic patients with ≤ 5 missing teeth, patients without cardiovascular disease, non-smoking patients, and patients receiving anti-diabetic drugs, α-carotene, lutein and zeaxanthin, or β-cryptoxanthin was also found to be related to periodontitis. Over 5 missing teeth, cardiovascular disease, smoking, and uncontrolled diabetes are greatly correlated with the higher incidence and progression of periodontitis ( 40 43 ) , which might overshadow or mask the relationship between carotenoid intake and periodontitis. Importantly, these groups of diabetic patients should pay more attention to their oral health, and higher intake of α-carotene, lutein and zeaxanthin, or β-cryptoxanthin may become a reference strategy in hindering the occurrence and development of periodontitis, which requires future studies to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the level of immunoglobulins in patients with diabetes mellitus and periodontitis occurs, most likely, due to stimulation of local production of immunoglobulins during prolonged activity of bacterial antigens in chronic periodontal diseases. Kranthi J. et al reported that an increase in Ig M concentration with a combination of diabetes and GP is associated with an enhanced immune system response to diabetic status in periodontitis [14,15,16]. The increased incidence of periodontitis in diabetic patients suggests that altered immune responses may contribute to the development of periodontitis in diabetic patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…Since 1993, severe periodontal disease has been considered the 6 th major complication of DM after CVD, eye disease, neuropathy, nephropathy, and peripheral vascular disease[ 13 ]. Being a state of immunocompromise, DM can worsen the virulence and invasiveness of pathogenic oral microbial flora aggravating the local inflammation and infection in those with periodontal disease[ 1 , 14 ]. Moreover, hyperglycemia-induced oxidative stress and the generation of reactive oxygen species in the periodontal tissues can aggravate local tissue damage and worsen periodontitis[ 14 ].…”
Section: Pathobiological Interlink Between Periodontitis and Dmmentioning
confidence: 99%
“…Being a state of immunocompromise, DM can worsen the virulence and invasiveness of pathogenic oral microbial flora aggravating the local inflammation and infection in those with periodontal disease[ 1 , 14 ]. Moreover, hyperglycemia-induced oxidative stress and the generation of reactive oxygen species in the periodontal tissues can aggravate local tissue damage and worsen periodontitis[ 14 ]. On the other hand, the chemical and immunological mediators released into the circulation as part of periodontal inflammation worsen systemic insulin resistance (IR) with worsening of DM.…”
Section: Pathobiological Interlink Between Periodontitis and Dmmentioning
confidence: 99%